2020
DOI: 10.1039/d0ra06038k
|View full text |Cite|
|
Sign up to set email alerts
|

Pharmacophore-based approaches in the rational repurposing technique for FDA approved drugs targeting SARS-CoV-2 Mpro

Abstract: Novel coronavirus (CoV) is the primary etiological virus responsible for the pandemic that started in Wuhan in 2019–2020.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
28
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(29 citation statements)
references
References 43 publications
1
28
0
Order By: Relevance
“…Figure 2 F presents the features developed in 6LU7 using MVD 6.0. This model was also authenticated using the previously reported model for M pro with well-defined training and a test set of compounds [ 9 ]. The RMSD value of 0.032882 Å indicated the robustness of the model for virtual screening experiments.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Figure 2 F presents the features developed in 6LU7 using MVD 6.0. This model was also authenticated using the previously reported model for M pro with well-defined training and a test set of compounds [ 9 ]. The RMSD value of 0.032882 Å indicated the robustness of the model for virtual screening experiments.…”
Section: Resultsmentioning
confidence: 99%
“…It is well documented that the M pro of SARS-CoV-2 is one of the most tempting drug targets, as viral maturation eventually depends mainly on the function of M pro [ 7 , 8 , 9 ]. The inhibition of M pro has been shown to obstruct viral replication in certain studies.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The protease is active as a homodimer, structured by the dimerization of two protomers designated as monomer A and monomer B, and the catalytic dyad in each protomer is defined by Cys145 and its residues (Zhang et al, 2020b). This has led to the development of multiple studies with experimental and computational approaches in search of possible inhibitors that can effectively block the activity of this protease (Balaramnavar et al, 2020;Dai et al, 2020;Gao et al, 2020;Jin et al, 2020a;Jin et al, 2020b;Ngo et al, 2020;Zhang et al, 2020b). Work with the 3C-like proteinase from SARS coronavirus revealed that the Cys145 residue is key at the active site of 3CLpro (Huang et al, 2004), this advance allowed the mentioned residue to be an attractive target for covalent ligands to bind acting as inhibitors of 3CL pro .…”
Section: Molecular Docking Analysismentioning
confidence: 99%
“…A recent virtual screening study on 2100 compounds from the CHEMBL database, ZINC database, and FDA-approved drugs and molecules under clinical trials followed by subsequent MD-simulation studies have shown that Cobicistat, Ritonavir, Lopinavir, and Darunavir would act as potent inhibitors of M pro [65] . Virtual screening and MD-studies have also identified other FDA-approved drugs [66] , [67] , [68] for the inhibition of M pro . However, in vivo studies of these ligands can only yield their true efficacy against M pro .…”
Section: Drug Targets Of the Main Protease (M Promentioning
confidence: 99%